Evaluación de la producción de fucosidasas por bifidobacterias - Rodríguez Nava, Omar (Universidad Autónoma Metropolitana, 2013)
El presente trabajo se enfoca en el estudio de las bifidobacterias capaces de producir fucosidasas con potencial para utilizarse en la síntesis de oligosacáridos semejantes a los encontrados en la leche humana.Las glicosil-hidrolasas, son enzimas capaces de sintetizar oligosacáridos con acción prebiótica. Entre estas enzimas, las fucosidasas son de especial interés debido a que pueden ser capaces de sintetizar oligosacáridos similares a los de la leche humana con importantes funciones biológicas como la inhibición de la adhesión de toxinas y patógenos al tracto gastrointestinal así como la promoción del crecimiento de bifidobacterias colónicas. Tales enzimas no se encuentran disponibles comercialmente, por ello, enel presente trabajo se evaluó la producción de fucosidasas de diversas cepas de bifidobacterias utilizando glucosa como fuentes de carbono: Bifidobacteriuminfantis 14431, B.infantis17930, B.longum, B. bifidus, B.animalis, B. lactis, B. breve yB. adolescentis.Los microorganismos se propagaron en medio TPY y se inocularon en medio MRS-cisteínapara la evaluación de la producción de fucosidasas. Se realizaron fermentacionesde 12 h tanto para su crecimiento como para su propagación a fin de tener al microorganismo en fase exponencial.El ensayo de actividad enzimática se llevó a cabo espectrofotométricamente, para ello se empleó como sustrato elpara-nitrofenil-fucósidoy se registró el incremento de la absorbancia con respecto al tiempo, se calculó la actividad enzimática de las cepas evaluadas. Las que presentaron actividad de -L-fucosida fueron: Bifidobacteriuminfantis 17930, B.infantis14461, B.longum yB.bifidus, por otro lado, las cepas que no presentarón actividad enzimática fueron: Bifidobacterium lactis, B.animalis, B.adolescentis, B.breve. Es deseable evaluar en un futuro la producción de fucosidasas en medios con diferentes fuentes de carbono y en particular en presencia de mucina además de proponer un método eficiente para la recuperación de la enzima intracelular. ; For some time scientists realized the great contributions and health benefits of microorganisms classified as probiotics, so these have become important and increasingly more products are included for the benefits they bring to the health of human. Among the microorganisms classified as probiotics Bifidobacterium genus find the microorganism which are more abundant in the newborn, these inhabit the intestine of humans in its infant stage because it can be developed from the oligosaccharides present in human breast milk, bringing great benefit to the host, such as: the reduction of pathogenic microorganisms in the digestive tract, the production of organic acids, reduces the duration of infectious diarrhea, microbiota balance, among others. Breast milk contains more than 130 different oligosaccharides, which constitute the third component thereof. Most abundant oligosaccharides in human milk are free (not conjugated) and neutral and also containing fucose. The fraction of undigested oligosaccharides in human breast milk stimulates the growth of bifidobacteria in the colon. This flora has beneficial effects and protection against enteric infections, so the fucooligosaccharides are an essential part of the innate immune system which protects against pathogens mother during lactation. as noted above the present study assessed the enzymatic activity and the production of enzymes fucosidases various strains belonging to this genus using glucose as a carbon source capable of producing enzymes that can catalyze fucosidasas enzymatic reactions to synthesize fucooligosaccharides similar to those present in the Human milk, for this purpose were evaluated eight strains of the genus Bifidobacterium as:B.infantis 14431, B. infantis17930,B.longum, B. bifidus,B. animalis, B.lactis, B. breve and B. adolescentis. For growth culture media were used MRSand also for propagation TPY medium. Fermentations of were conducted for 12 hours so as to increase its spread, in order to have the organism in exponential phase, and thus perform the enzymatic activity assay was performed spectrophotometrically for this fucoside Nitrophenolwas used in concentration of 1mg/mL. In the cell for carrying out the test were placed 900μL of PNP-fucoside and 100µL of fermented medium. Thus was obtained the increase in absorbance over time, also performed a standard curve for the PNP-fucoside concentration calculations, these data further enzyme activity was calculated from the strains that showed enzymatic activity, these enzymes were Bifidobacterium infantis 14431,B. infantis17930, B. longum and B. bifidus.